Genome-Wide Analysis of DA1-Like Genes in Gossypium and Functional Characterization of GhDA1-1A Controlling Seed Size - Yang, Shuxian; Huang, Li; Song, Jikun; Liu, Lisen; Bian, Yingying; Jia, Bing; Wu, Luyao; Xin, Yue; Wu, Man; Zhang, Jinfa; Yu, Jiwen; Zang, Xinshan (Frontiers in Plant Science, 2021)
Cotton (Gossypium spp.) is an economically important crop grown for natural fibre and seed oil production. DA1 is a ubiquitin receptor that determines final seed and organ size by restricting the period of cell proliferation. In the present study, we identified 7 DA1-like genes each in cultivated tetraploid (AADD) G. hirsutum and G. barbadense, and 4 and 3 DA1-like genes in their ancestral diploid G. arboreum (A2A2) and G. raimondii (D5D5), respectively. The 7 GhDA1 genes were confirmed to be distributed on four At and three Dt subgenome chromosomes in G. hirsutum. GhDA1-1A showed a high sequence similarity to AtDA1 in Arabidopsis, and they possessed the same functional domains, suggesting conserved functions. The overexpression of GhDA1-1AR301K in Arabidopsis significantly increased seed size and seed weight, indicating that GhDA1-1A is a promising target for cotton improvement. This study provides information on the molecular evolutionary properties of DA1-like genes in cotton, which will be useful for the genetic improvement of cotton.